Real-time air concentrations and turbulent fluxes of volatile organic compounds (VOCs) over historic closed landfills to assess their potential environmental impact. (15th September 2022) - Manco, Antonio; Ciccioli, Paolo; Famulari, Daniela; Brilli, Federico; Ciccioli, Piero; Tommasi, Paul Di; Toscano, Piero; Gioli, Beniamino; Esposito, Andrea; Magliulo, Vincenzo
Abstract: For the first time, emission/deposition fluxes of volatile organic compounds (VOCs) and H2 S from a historic closed landfill site in Southern Italy were determined by Eddy Covariance (EC) using Proton Transfer Reaction Time-of-Flight Mass Spectrometry (PTR-TOF-MS). This was done in two field campaigns of one week performed in July and October 2016, where fluxes of CO2 and CH4 were also measured. Many compounds not previously identified in the biogas were detected by PTR-TOF-MS, but only in July some of them produced positive fluxes exceeding the flux limit of detection. Methanol was the most emitted compound with an average flux of 44.20 ± 4.28 μg m −2 h −1, followed by toluene with a mean flux of 18.97 ± 2.47 μg m −2 h −1 . Toluene fluxes were 10 times higher than those of benzene, fitting rather well with values previously measured in the biogas. VOCs emission fluxes of monoterpenes and highly reactive arenes did not reflect, however, the biogas composition. This, combined with tiny emissions of VOC oxidation products, suggests that landfill emissions underwent some photochemical degradation before being dispersed in the atmospheric boundary layer (ABL). Deposition fluxes of some VOCs emitted from the sea was also observed in July. No relevant VOC fluxes were instead measured in October, suggesting that temperature was the variable controlling most landfill emission. Albeit small, summer landfill emissions from the investigated site can have an impact on the population living nearby, because they contain or still generate compounds that causing nuisance. Graphical abstract: Image 1 Highlights: VOCs from landfills by Proton Transfer Reaction Time-of-Flight Mass Spectrometer. Eddy Covariance turbulent fluxes of VOCs, CO2 and CH4 from landfills. Summer fluxes of VOCs and H2 S not previously identified in the biogas were measured. No relevant fluxes of VOCs and H2 S were measured in autumn. Methanol was the most emitted compound followed by toluene.